Self-assembled insulin and nanogels polyelectrolyte complex (Ins/NGs-PEC) for oral insulin delivery: Characterization, lyophilization and in-vivo evaluation - Mudassir, Jahanzeb; Yusrida, Darwis; Suriani, Muhamad; Khan, Arshad Ali (Dovepress, 2019)
Introduction: Insulin is given by injection, because when administered orally, it would be destroyed by enzymes in the digestive system, hence only about 0.1% reaches blood circulation. The purpose of the present study was to use pH sensitive polyelectrolyte methyl methacrylate (MMA)/itaconic acid (IA) nanogels as carriers in an attempt to improve absorption of insulin administered orally. Methods: Insulin (Ins) was incorporated into the MMA/IA nanogels (NGs) using the polyelectrolyte complexation (PEC) method to form Ins/NGs-PEC. Several parameters, including Ins:NGs ratio, pH, incubation time and stirring rate were optimized during preparation of InsNGs-PEC. The prepared formulations were characterized in terms of particle size (PS), polydispersity index (PdI), zeta potential (ZP) and percent entrapment efficiency (% EE). Results: The optimized InF12 nanogels had a PS, PdI, ZP and %EE of 190.43 nm, 0.186, −16.70 mV and 85.20%, respectively. The InF12 nanogels were lyophilized in the presence of different concentrations of trehalose as cryoprotectant. The lyophilized InF12 containing 2%w/v trahalose (InF12-Tre2 nanogels) was chosen as final formulation which had a PS, PdI, ZP and %EE of 430.50 nm, 0.588, −16.50 mv and 82.10, respectively. The in vitro release of insulin from InF12-Tre2 nanogels in the SGF and SIF were 28.71% and 96.53%, respectively. The stability study conducted at 5±3°C for 3 months showed that lnF12-Tre2 nanogels were stable. The SDS-PAGE assay indicated that the primary structure of insulin in the lnF12-Tre2 nanogels was intact. The in-vivo study in the diabetic rats following oral administration of InF12-Tre2 nanogels at a dose of 100 IU/kg body weight reduced blood glucose level significantly to 51.10% after 6 hours compared to the control groups. Conclusions: The pH sensitive MMA/IA nanogels are potential carriers for oral delivery of insulin as they enhanced the absorption of the drug.